2015
DOI: 10.3109/14767058.2015.1053449
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome of singleton versus twin late preterm infants: do twins mature faster than singletons?

Abstract: We found no evidence to support the traditional belief that twin late preterm infants have accelerated maturation and better neonatal outcome compared with singleton late preterm infants. Our findings suggest that late preterm twins have a prognosis similar to that of singleton late preterm infants born at the same gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
2
13
1
Order By: Relevance
“…The mode of delivery in twin pregnancy is still controversial [ 10 19 20 ]; however, cesarean section is preferred in our institution because of safety concerns. In neonatal characteristics, mean birth weight was smaller in twin groups similar to previous studies [ 7 17 ]. The growth of twins differed from that of singleton after 33 weeks of gestation [ 22 ] and twin fetuses were expected to be approximately 121 go lighter than singleton on average [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The mode of delivery in twin pregnancy is still controversial [ 10 19 20 ]; however, cesarean section is preferred in our institution because of safety concerns. In neonatal characteristics, mean birth weight was smaller in twin groups similar to previous studies [ 7 17 ]. The growth of twins differed from that of singleton after 33 weeks of gestation [ 22 ] and twin fetuses were expected to be approximately 121 go lighter than singleton on average [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…And the authors suggested that this result would be associated with acceleration of lung maturation and higher rate of antenatal corticosteroid administration in twin group [ 17 ]. On the other hand, Ribicic et al [ 7 ] reported there were no differences in the rate of TTN and RDS despite of higher rate of cesarean delivery in twin group. And they also suggested this result would be a higher rate of antenatal corticosteroid administration and of higher rate female gender in twin group.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations